Nutritional vitamin D is efficacious for reducing intact Parathyroid hormone in chronic kidney disease, a prospective interventional study - Memon, Shoukat; Ashar Alam; Salman Imtiaz (Journal of the Pakistan Medical Association, 2022)
Objective: To see the efficacy of oral cholecalciferol administered to chronic kidney disease patients with vitamin D deficiency. Methods: The prospective interventional study was conducted at the Indus Hospital, Karachi, from January 11, 2017, to January 10, 2018, and comprised diagnosed pre-dialysis chronic kidney disease patients of either gender aged >14 years having vitamin D deficiency. Oral vitamin D 50,000IU was given weekly to those who had severe deficiency <10ng/ml, and every other week to those with less severe 10-25ng/ml deficiency for 3 months. Improvement in vitamin D level was checked along with other chronic kidney disease markers every month over the 3-month period. Data was analysed using SPSS 24. Results: Of the 186 patients enrolled, 129(%) completed the study; 76(58.5%) males and 53(40.8%) females. Overall, 105(81.4%) patients achieved normal vitamin D levels after 3 months of treatment. Significant negative but weak correlation of phosphate, creatinine and intact parathyroid hormone levels was found with vitamin D (p<0.05). Significant positive but weak correlation was found between albumin and vitamin D levels (p<0.05). Conclusion: Significant efficacy of oral vitamin D in chronic kidney disease patients was seen.